The Influence of Father Involvement on the Psychological Well-Being of Early Adult Women Raised Without a Father Figure - Evita Olda Gloria Sinaga; Togi Fitri A. Ambarita (CV Putra Publisher, 2025)
This study aims to determine the Influence of Father Involvement on the Psychological Well-Being of Early Adult Women Raised Without a Father Figure. Based on research conducted by researchers, with the title of research on the influence of father involvement on the psychological well-being of early adult women raised without a father figure. It can be concluded that: Based on descriptive results, most respondents have a moderate level of father involvement. This shows that even though respondents have lost a father figure, some of them still have sufficient experience of father involvement before their father died. The level of psychological well-being of respondents is also mostly in the moderate category. This shows that respondents have a fairly good psychological well-being condition, although not optimal in various aspects such as self-acceptance, social relationships and independence. The results of the hypothesis test show that there is a significant influence between father involvement on psychological well-being in early adult women raised without a father figure. This is proven by a significant value of 0.000 (p<0.05). The coefficient of determination (R square) value of 0.402 shows that father involvement contributes 40.2% to psychological well-being, thus the higher the level of father involvement felt by the individual, the better the level of psychological well-being. The remaining 59.8% is influenced by other factors not examined in this study.